Transverse sinus air after cranial trauma - Cihangiroglu, M; Ozdemir, H; Kalender, O; Ozveren, F; Kabaalioglu, A (Elsevier Ireland Ltd, 2003)
Air in vascular compartments has been rarely reported. We report a case in whom air within transverse sinus and sinus confluence through ruptured superior sagittal sinus (SSS) due to fractures of parietal and frontal bones was disclosed by computed tomography (CT). Although air in transverse sinus has been reported rarely this could be the first case with air in transverse sinus through the SSS after cranial trauma. (C) 2003 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: intravascular air; transverse sinus; cranial trauma; computed tomography